DIVERSITY OF TREE TYPES IN THE FOREST AREA OF LAMPAGEU UJONzxG PANCU VILLAGE, ACEH BESAR REGENCY - Eva Nauli Taib,; Raihan Amalia,; Ulfa Nurjannah,; Ruli Ariangga,; Silva Mailinda, (Proceeding International Conference on Biology, Technology, Science and Education, 2024)
Research efforts on "Tree Species Diversity in the Forest Area of Lampageu Ujong Pancu Village, Aceh Besar Regency" were carried out in June 2023. The aim of conducting research on Tree Species Diversity in the Forest Area of Lampageu Ujong Pancu Village, Aceh Besar Regency is to identify the types and diversity of trees found in that region. The research steps taken were to identify tree species in the research area and calculate the tree diversity index in the Lampageu Ujong Pancu Village Forest Area, Aceh Besar Regency. The method used in this research is an exploratory survey method by making direct observations at the location and object of observation. The data collection technique uses the transect method (line transect). Research data was analyzed using the diversity index formula with the Shannon Wiener formula. The results of the research show that there are 37 species which are members of 27 families and consist of 68 individuals who live in the research location. Flacourtia jangomas and Terminalia oblong as many as 6 individuals. The family that has a relatively large number of species is Anacardiaceae, 5 species.